Situational Analysis: Existential and Interpretative Perspective - Мельніков, Андрій Сергійович; Мельніков, А. С.; Мельников, Андрей Сергеевич; Melnikov, Andrii S.; Джонсон, Джон Міртон; Johnson, John Myrton; Johnson, John M. (Emerald Publishing Limited, 2022)
Existentialist progenitors emphasized the contextual or situational nature of human action and meaning. This paper reviews some of these ideas and then compares how different approaches in sociology have embodied this view: symbolic interaction, dramaturgy, ethnomethodology, the California School of Existential Sociology, grounded theory methodology, and macro existential sociology. These perspectives will be compared to assess their relative emphases on the contextual or situational nature of human action and meaning.

Прабатьки екзистенціалістів підкреслювали контекстну або ситуативну природу людської діяльності та змісту. У цій статті розглядаються деякі з цих ідей, а потім порівнюється, як різні підходи в соціології втілюють цю точку зору: символічна взаємодія, драматургія, етнометодологія, Каліфорнійська школа екзистенційної соціології, методологія обґрунтованої теорії та макроекзистенційна соціологія. Ці точки зору будуть порівнюватися, щоб оцінити їх відносні акценти на контекстуальній або ситуаційній природі людської діяльності та змісту.
Melnikov A. S. Situational Analysis: Existential and Interpretative Perspective / A. S. Melnikov, J. M. Johnson // Studies in Symbolic Interaction. - Vol. 53. - Emerald Publishing Limited, 2022. – P. 135-149.
Keywords: situational analysis; interpretative paradigm; existential sociology; symbolic interaction; dramaturgy; ethnomethodology; grounded theory; ситуаційний аналіз; інтерпретативна парадигма; екзистенційна соціологія; символічна взаємодія; драматургія; етнометодологія; обґрунтована теорія; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Sociology